CLINICAL CASE OF CO-INFECTION CAUSED BY HEPATITIS B АND D IN A CHILD OF THE FIRST YEAR OF LIFE - T. V. Cherednychenko; O. V. Molochkova; G. V. Chaplygina; O. B. Kovalev; L. I. Konovalova (LLC "Diagnostics and Vaccines", 2015)
The article presents a case of own observation of a child in the first year of life with co-infection of hepatitis viruses B and D. The child was born to a mother with chronic hepatitis B and D. The co-infection was typical and mild. The treatment was carried out with interferon-α2b - viferon (rectal suppositories) in a daily dose of 1 mio IU during 6 months. The outcome of the disease was recovery with elimination of the pathogen.